A new geographical distribution of coffee production? Analysis of the concentration and specialization of coffee production (Coffea arabica) in Colombian municipalities between 2007 and 2021 - Mora-Villalobos, Carlos Albeiro; Jara-Rojas, Roberto (Revista de Geografía Norte Grande, 2025)
Colombian coffee is produced in 629 out of 1,121 municipalities and accounted for 0.6% of the national Gross Domestic Product (GDP) in 2021, equivalent to 8.9% of the agricultural GDP. This study analyzes the concentration and specialization of coffee production in Colombian municipalities between 2007-2021 to identify coffee’s agricultural clusters (AC). The methodology includes the analysis of four statistical databases applying the Gini coefficient, Location Quotient (LQ), Herfindahl-Hirschman Index (HHI), and Moran’s Index to identify the AC in the Colombian coffee sector, complemented by bivariate thematic cartography. Additionally, we link coffee production, LQ, and HHI with the Multidimensional Poverty Index (MPI) for 2018, and average annual temperature (AAT) and average annual precipitation (AAP) with a small sample of municipalities. The results reveal that in 2021, the regional Gini was 0.71, and the municipal Gini was 0.80. A total of 416 municipalities were identified with an LQ greater than 1.0, of which 78 are among the top 20% with the highest values. The average HHI was 0.151, ranging from 0 to 0.879. Additionally, MPI shows higher levels in rural areas and a low correlation with LQ and HHI. Average annual temperature and precipitation have a low correlation with HHI and LQ. A significant concentration of coffee production is observed in the municipalities of Huila, Antioquia, Cauca, Tolima, Caldas, and Santander accounting for 70.4% of total production. Likewise, we found that multidimensional poverty is high in rural areas of coffee-growing municipalities (average 48.0%, maximum 93.2%, minimum 9.2%). We established that the variables with the highest incidence were low educational achievement, informal work, and lack of access to improved water sources. These results should be of interest to regional and municipal governments, guild institutions, and public policymakers in agriculture, especially concerning climate change, production costs, associativity programs, agro industrial promotion, and quality based commercialization strategies.